Using conflict negativity to index psychological tension between impartiality and status-upholding principles. (3rd September 2021) - Plaks, Jason E.; Lv, Jianing; Zhao, Mingjun; Staples, William; Robinson, Jeffrey S.
ABSTRACT: People often endorse the moral principle that all human lives are equally valuable. At the same time, people often privilege high-status individuals over low-status individuals. These two inclinations come into conflict in a scenario involving the potential killing of a high-status person to save the lives of multiple low-status people. In the present study, participants viewed a series of sacrificial dilemmas in which the social status of the victims and beneficiaries was varied. We measured participants' choice (sacrifice vs. don't sacrifice), response time, and electroencephalographic activity, with an emphasis on conflict negativity (CN). Overall, we found no effects of victim/beneficiaries status on choice and response time. However, participants displayed a more pronounced CN effect when contemplating a high-status victim/low-status beneficiaries tradeoff than a low-status-victim/high-status beneficiaries tradeoff. Further analyses revealed that this effect was primarily driven by participants who endorsed deontological principles (e.g., "Some rules must never be broken, no matter the consequences"). In contrast, those who endorsed utilitarian principles displayed equivalent levels of conflict negativity, regardless of the social status of victims and beneficiaries. These findings shed light on the role of conflict in the phenomenology of moral decision making.